Effect of Beet and Lemon Juice on Increasing Hb Levels in Anemia Pregnant Women at the Tanjung Langkat Health Center in 2024 - Maulidanita, Riska; Hadya, Rizca Annur (Journal of Midwifery and Nursing, 2025)
The absence of red blood cells in the body is known as anemia. Anemia during pregnancy increases the risk of postpartum hemorrhage in expectant mothers. The results of the initial survey at the Tanjung Langkat Health Center in March 2024 showed that there were 24 pregnant women and 5 pregnant women were found to have anemia in TM 3. Beetroot juice is one of the many strategies pregnant women can use to avoid anemia. This study aims to ascertain how beet juice affects pregnant women with anemia by raising their hemoglobin levels. An experimental quasy design is a type of experiment that does not fully control all external variables (as in a fully randomized experiment), but still attempts to test a cause-and-effect relationship. In the pretest and posttest one group method, there is only one experimental group that is measured twice, namely before and after treatment (intervention). Based on the results of the study, Giving pregnant women with anemia beet and lemon juice has the effect of raising their hemoglobin levels. The majority of expectant mothers who drink this juice see a marked rise in hemoglobin levels. To raise awareness and knowledge of pregnant women, more education is required regarding the significance of preventing anemia during pregnancy and the choice of foods and drinks that encourage rising hemoglobin levels.